Are There Differences in the Anthropometric, Hemodynamic, Hematologic, and Biochemical Profiles between Late- and Early-Onset Preeclampsia? - Márcia Aires Rodrigues de Freitas; Alice Vieira da Costa; Luciana Alves de Medeiros; Mario da Silva Garrote Filho; Angélica Lemos Debs Diniz; Nilson Penha-Silva (Obstetrics and Gynecology International)
Preeclampsia (PE) is classified as early-onset PE (EOPE) and late-onset PE (LOPE) when present before or after 34 weeks of gestation, respectively. This transversal study aimed to investigate the differences and possible associations existing in the anthropometric, hemodynamic, hematologic, and biochemical profiles of late- and early-onset preeclampsia. The study included 65 volunteers admitted to a tertiary hospital in Brazil: 29 normotensive and 36 with preeclampsia (13 with EOPE and 23 with LOPE). Pregnant women with LOPE presented greater weight gain and borderline increase in body mass index at the end of gestation in relation to the other groups, which is compatible with the metabolic origin, associated with obesity, attributed to this form of the disease. Pregnant women with EOPE presented a borderline reduction in the number of erythrocytes and a significant decrease in the number of platelets, in addition to a significant increase in reticulocytes, serum iron, and ferritin when compared to normotensive pregnant women and pregnant women with LOPE. A significant increase in osmotic stability of erythrocytes was observed in the EOPE group in relation to other groups. Hemodynamic analysis by Doppler ultrasonography of the ophthalmic artery showed that both groups of pregnant women with PE presented alterations compatible with the occurrence of hyperflow in the orbital territory. These hemodynamic changes were associated with changes in hematimetric indices.